Study of the impact of waste glasses types on pozzolanic activity of cementitious matrix. (10th February 2019) - Bouchikhi, Abdelhadi; Benzerzour, Mahfoud; Abriak, Nor-Edine; Maherzi, Walid; Mamindy-Pajany, Yannick
Highlights: Packing density model applied to fine materials make it possible to optimize granular structure. Mechanical properties of mortars based on glass wastes remain in the same order of standards mortar. This study allows to establish that the three waste glasses present a beneficial pozzolanic effect for cementitious matrix. Leaching tests confirm the presence of available silica in large amount in VP compared to other samples (OS and EWW), which remains coherent with mechanical results. Abstract: This paper deals with glass packaging and especially with different types of wastes from its recycling (Valued Product (VP), End-of-Wash Waste (EWW) and Optical Sorting (OS)), in order to make a comparative study of their pozzolanic activity and leaching behaviour for an environmental study. VP is used by industrials in the production of new packaging glass, and EWW and OS are residues which are not currently valued, so considered as undesirable parts. First of all, these three materials have been crushed to obtain a homogeneous particle-size distribution (with d50 = 6.5 µm). Then, they have been physically and chemically characterized by helium pycnometer (absolute density), gas adsorption method (specific surface), X-ray crystallography and X-ray Fluorescence for chemical composition. The second step of this study involves making 4 × 4 × 16 cm specimens according to standard NF EN 196-1 in order to compare a reference mortar (RM) with 100% of cement 42.5 R with samples including the three types of waste glass (VP, EWW and OS) in partial substitution of cement. Leaching tests performed on these wastes according to standard NF EN 12457-2 allowed to highlight a correlation between mobility of silicon, aluminium and calcium, and the mechanical performances obtained. Finally, SEM observations and study of cement paste in fresh state allowed to give an explanation of the results observed in macroscopic scale.